OP0301 C-X-C MOTIF CHEMOKINE 10 (CXCL10) IS A POTENTIAL BIOMARKER OF DISEASE ACTIVITY IN PSORIATIC ARTHRITIS (PSA). (June 2019) - Machhar, Rohan; Oke, Sofia; Ye, Justine; Abji, Fatima; Chandran, Vinod
Abstract : Background: Assessment of Psoriatic Arthritis (PsA) disease activity requires detailed clinical evaluation complemented by imaging. Current laboratory markers such as CRP do not accurately reflect PsA disease activity. Identifying soluble biomarkers of PsA disease activity is an important perceived clinical need. Objectives: We aimed to identify markers that correlates with PsA disease activity and change with treatment. Methods: Serum samples were obtained from a cohort of patients with PsA not on DMARD treatment assessed clinically every 6 months according to a standard protocol including several measures of disease activity: physician and patient global assessment, tender and swollen joint counts, skin scores (BSA, PASI) and the composite measures- Disease Activity Score for PsA (DAPSA) and PsA Disease Activity Score (PASDAS). In the discovery phase, we mined our clinical and biomarker database that has linked biomarker and disease activity measures and identified markers that potentially reflect PsA disease activity. In verification phase 1 we measured the selected 17 markers in 80 PsA samples. 8 Markers that significantly correlated with disease activity were identified based on Spearman correlation coefficients. In the verification phase 2 these 8 markers were further assayed in an inception cohort of 80 patients. In this phase, physician global assessment of disease activity (including skin and joints-MDGA) was used as the primary measure of disease activity; other skin, MSK and patient reported measures were considered secondary measures. In verification phase 3 with the hypothesis that markers associated with disease activity would decrease with treatment, the markers that correlated with MDGA where further assayed in 40 patients before and after 6 months of treatment (26 biologics and methotrexate, 14 methotrexate). All assays were done using commercially available ELISA. Results: In verification phase 1 8 markers of 17 tested were found to be associated with measures of disease activity in 80 PsA patients (mean age 47, males 58%, swollen joint count [SJC] 2, tender joint count [TJC] 3.6, PASI 2.9). In verification phase 2 2 markers [CXCL10 (ρ=0.25, p =0.03) and CRP (ρ=0.26, p =0.02)] tested in 80 patients (mean age 49, males 54%, SJC 1.5, TJC 3.3, PASI 5.6) correlated with MDGA, and did not correlate with each other. Three other markers correlated with secondary measures; COMP correlated with PASDAS (ρ=0.22, p =0.04), MMP3 correlated with PASI (ρ=0.27, p =0.01) and CPII-C2C ratio correlated with active joints (ρ= -0.27, p =0.02). In verification phase 3 CXCL10 (baseline mean =246.7(standard deviation 190.79) - 6 month 177.7 (163.8)); (p=0.0008) and CRP (18.5 (19.1) - 9.5 (8.9)); (p=0.002)] significantly decreased 6 months post treatment. Conclusion: CXCL10, a marker previously associated with PsA, may also be a marker of PsA disease activity. Identifying a robust outcome measure for disease activity to conduct biomarker studies in a heterogeneous disease like PsA remains a significant challenge. Disclosure of Interests: None declared